The relationship between oil price and stock market return / Nur Hidayah Md Yusof - Md Yusof, Nur Hidayah (Faculty of Business and Management, 2011)
Previous research has been conducted in order to investigate the relationship between macroeconomic variables and emerging stock market return in literatures such as Sadorsky (2006). This study tries to analyse the relationship between oil price and stock market return in Malaysia. In a business anything done financially affects cash eventually. The objectives for this study s to investigate the relationship between the oil price and stock market return. The data of crude oil price and stock market return range from year 2006 until year 2010, and the data were derived from software Data Stream and Bank Negara. The result of simple regression analysis showed that, there is a positive relationship between crude oil price and stock market return.